Expanding magnetic organelle biogenesis in the domain Bacteria - Lin, Wei (Microbiome, 2020)
BACKGROUND: The discovery of membrane-enclosed, metabolically functional organelles in Bacteria has transformed our understanding of the subcellular complexity of prokaryotic cells. Biomineralization of magnetic nanoparticles within magnetosomes by magnetotactic bacteria (MTB) is a fascinating example of prokaryotic organelles. Magnetosomes, as nano-sized magnetic sensors in MTB, facilitate cell navigation along the local geomagnetic field, a behaviour referred to as magnetotaxis or microbial magnetoreception. Recent discovery of novel MTB outside the traditionally recognized taxonomic lineages suggests that MTB diversity across the domain Bacteria are considerably underestimated, which limits understanding of the taxonomic distribution and evolutionary origin of magnetosome organelle biogenesis. RESULTS: Here, we perform the most comprehensive metagenomic analysis available of MTB communities and reconstruct metagenome-assembled MTB genomes from diverse ecosystems. Discovery of MTB in acidic peatland soils suggests widespread MTB occurrence in waterlogged soils in addition to subaqueous sediments and water bodies. A total of 168 MTB draft genomes have been reconstructed, which represent nearly a 3-fold increase over the number currently available and more than double the known MTB species at the genome level. Phylogenomic analysis reveals that these genomes belong to 13 Bacterial phyla, six of which were previously not known to include MTB. These findings indicate a much wider taxonomic distribution of magnetosome organelle biogenesis across the domain Bacteria than previously thought. Comparative genome analysis reveals a vast diversity of magnetosome gene clusters involved in magnetosomal biogenesis in terms of gene content and synteny residing in distinct taxonomic lineages. Phylogenetic analyses of core magnetosome proteins in this largest available and taxonomically diverse dataset support an unexpectedly early evolutionary origin of magnetosome biomineralization, likely ancestral to the origin of the domain Bacteria. CONCLUSIONS: These findings expand the taxonomic and phylogenetic diversity of MTB across the domain Bacteria and shed new light on the origin and evolution of microbial magnetoreception. Potential biogenesis of the magnetosome organelle in the close descendants of the last bacterial common ancestor has important implications for our understanding of the evolutionary history of bacterial cellular complexity and emphasizes the biological significance of the magnetosome organelle.